Anxiety and depression level of patients with multidrug-resistant tuberculosis (MDR-TB) in two hospitals in Banten province, Indonesia - Tirta Darmawan Susanto; Allen Widysanto; Darien Alfa Cipta; Arron Tanara; Ghivarell Rizkie Wirawan; Adeline Bercadina Kosim; Christabella Maria Djoni; Ervinna Tantri; Chandni Kumar; Chelsie Angelius (Elsevier, 2023)
Purpose: Anxiety and depression can be found in patients diagnosed with multidrug-resistant Tuberculosis (MDR-TB). The purpose of this research is to measure the level of anxiety and depression in new patients with MDR-TB. Methods: One hundred two new patients newly diagnosed with MDR TB in two hospitals in Banten province, Indonesia, are measured for depression and anxiety symptoms. The measurements used the Indonesian language version of the Zung Anxiety Self-Assessment Scale Questionnaire and the Indonesian version of Zung Self-Rating Depression Scale Questionnaire for Pulmonary Tuberculosis Patients that have been validated. The results include the demographic data presented descriptively as tables and charts. Results: The mean age of the patients is 39,57+12,48 years. The monthly income of the patients is 54,9% low and 45,1% medium with no high income. Male is 61,8%, and 38,2% are female. The mean score of the anxiety index is 57,32+10,23. The mean score of the depression index is 55,02+12,36. The percentage of patients with no anxiety is 13,7%, minimal to moderate anxiety 46,1%, marked to severe anxiety 33,3%, and most extreme anxiety 6,9%. Conclusions: A significant proportion of patients newly diagnosed with MDR-TB experience anxiety and depression.